Enhancing Climate-Resilient Farming in Indonesia: The Roles of Crop Diversification, Agroforestry Adoption, Environmental Literacy, and Farmer Cooperative Participation (West Science Agro, 2026)
This study examines the role of crop diversification, agroforestry implementation, environmental literacy, and farmer cooperative participation in promoting climate-resilient agriculture in Indonesia. Climate change has increasingly affected agricultural productivity, environmental sustainability, and farmer livelihoods through droughts, floods, irregular rainfall patterns, and land degradation. A quantitative research approach was employed using a survey of 250 farmers from several agricultural regions in Indonesia. Data were collected using structured questionnaires with a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 4). The findings indicate that crop diversification positively and significantly influences climate-resilient agriculture Agroforestry implementation was found to have the strongest influence. Environmental literacy also demonstrated a significant positive effect, while farmer cooperative participation significantly affected climate-resilient agriculture. The model showed strong explanatory power with an R-square value of 0.742, indicating that the independent variables explained 74.2% of the variance in climate-resilient agriculture. The results highlight the importance of integrating sustainable farming practices, environmental awareness, and institutional collaboration to strengthen agricultural resilience and sustainability in Indonesia.